Non –English Major Undergraduate Students’ Perception towards Using Drama to Overcome Foreign Language Classroom Anxiety: A Case of Thai – Nichi Institute of Technology - Jittisukpong, Pisit (วารสารวิชาการมหาวิทยาลัยการจัดการและเทคโนโลยีอีสเทิร์น, 2019)
Non-native speakers (NNS) always show reluctance when they have to speak in English. We can say that they suffer the anxiety to express themselves in a foreign language. The fear or anxiety from real or expected communication by a student with another person or group has been defined as Foreign Language Anxiety (FLA). The purposes of the study were 1) to investigate the students’ attitude of Thai undergraduates who were not in an English major course towards drama related activities in class at Thai-Nichi Institute of Technology and 2) to identify the students’ perception towards the impacts of using drama presentation on students’ ForeignLanguage Classroom Anxiety Level at Thai-Nichi Institute of Technology. The samples were 30 first year students who studied an English Foundation Course and came from different faculties at TNI in the first semester of the academic year 2018. All of them were non - English major students and they were selected for purposive sampling based on the class assigned for the researcher by the university registrar’s office. The data was collected through a survey questionnaire. The results of the research indicated that the students regarded drama as a fun activity. They did not feel any anxiety during the drama class. Moreover, they felt more relaxed when they spoke English in front of people after several weeks of drama training.